2012
DOI: 10.2458/jmm.v3i1.16110
|View full text |Cite
|
Sign up to set email alerts
|

Problems in Using Diagnosis in Child and Adolescent Mental Health Services Research

Abstract: This paper presents results from a three-part study on diagnosis of children with affective and behavior disorders. We examined the reliability, discriminant, and predictive validity of common diagnoses used in mental health services research using a research diagnostic interview. Results suggest four problems: a) some diagnoses demonstrate internal consistency only slightly better than symptoms chosen at random; b) diagnosis did not add appreciably to a brief global functioning screen in predicting service us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The findings of the present study substantiate previous research which suggests that the child's demographic characteristics, such as gender, age, and ethnicity, are not associated with treatment responses (Anderson et al, 2008;Bickman et al, 2002;Dalsgaard et al, 2002;Rosenblatt & Furlong, 1998;Southam-Gerow et al, 2001;Walrath et al, 2001). Prior research (Jacobs et al, 2008) has revealed that the presence of internalizing disorders were associated with poorer response to treatment in children with ED.…”
Section: Changes In Functioningsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of the present study substantiate previous research which suggests that the child's demographic characteristics, such as gender, age, and ethnicity, are not associated with treatment responses (Anderson et al, 2008;Bickman et al, 2002;Dalsgaard et al, 2002;Rosenblatt & Furlong, 1998;Southam-Gerow et al, 2001;Walrath et al, 2001). Prior research (Jacobs et al, 2008) has revealed that the presence of internalizing disorders were associated with poorer response to treatment in children with ED.…”
Section: Changes In Functioningsupporting
confidence: 89%
“…Similarly, Walrath and colleagues (2001) found boys and girls with ED did not differ in their mental health functioning after receiving partnership system of care services. Further support for the insignificant impact of age on treatment support was found in Bickman, Andrade, and Lambert (2002) study of 125 children with ED who received specialty home-based services akin to CPSR.…”
Section: Child Characteristics and Treatment Outcomesmentioning
confidence: 93%
“…Alternative approaches to these norm-based trajectories come with their own difficulties. We could attempt to characterise dose-response relationships to see if more treatment sessions leads to greater improvement (Bickman, Andrade, & Lambert, 2002). However, this kind of observational study is prone to bias as duration of attendance may be positively or negatively correlated to surrogate factors affecting outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation problems posed by the presence of comorbidities in children and adolescents with mental health issues, for instance, is illustrated in Bickman et al study. 152 A large percent (40%) of their sample's comorbid condition test scores were practically inseparable from the suspected disorder test result making identification of a single primary diagnosis that characterizes the child's problems exceedingly difficult. Furthermore, in an editorial to a special issue, 153 the authors note that, although in children 3-5 in particular, comorbidity is the rule rather than the exception, when an NDD is suspected, children will be seen by one specialist at a time despite the frequent presence of additional problems in this age group.…”
Section: Calls For Change In Asd Diagnosis and Intervention With Childrenmentioning
confidence: 99%